Presencia de micorrizas en orquídeas de un jardín botánico neotropical - Rivas, Marta (Universidad de Costa Rica, 1998)
Mycorrhizal occurrence was tested in roots of 24 terrestrial and epiphytic orchid species growing at the Lankester Botanical Gardens (Cartago, Costa Rica). Standard staining and light microscopy were used to search for pelotons. Roots in contact with the substrate harbor extensive mycorrhyzal fungi. There may be a wide distribution and density of the fungal flora in the secondary forests of the site, this could explain the high natural regeneration of orchids on the garden.